Facilitated acquisition of eyeblink conditioning in those vulnerable to anxiety disorders - Caulfield, Meghan D.; McAuley, J D.; Servatius, Richard J. (Frontiers in Human Neuroscience, 2013)
Behavioral inhibition (BI) increases vulnerability to develop anxiety disorders and is typified by avoidance and withdrawal from novel objects, people, and situations. The present study considered the relationship between behavioral inhibition and temperamental risk factors, such as trait anxiety and acquisition rate of a classically conditioned eyeblink response. 174 healthy undergraduate students (mean age 20.3 years, 71.8% female) were given the State-Trait Anxiety Inventory and a battery of self-report measures of behavioral inhibition consisting of the Adult and Retrospective Measures of Behavioural Inhibition (AMBI/RMBI) and the Concurrent and Retrospective Self Report of Inhibition (CSRI/RSRI). Participants then underwent standard delay classical eyeblink conditioning consisting of 45 trials with a 500-ms CS overlapping and co-terminating with a 10-ms airpuff US. Individuals with higher scores on the AMBI and Trait Anxiety Inventory, but not the other measures, showed faster acquisition of a conditioned eyeblink response than individuals with lower scores. Results support a relationship between facilitated acquisition of inter-stimulus relationships and risk for anxiety, and suggest that some measures assessing anxiety vulnerability better capture this relationship than others.